The Effect of Overcrowding on Nurses' Work Stress and Patient Satisfaction in The Emergency Group of Hermina Hospital Jatinegara - Silitonga, Junita Maratur; Anugrahwati, Ria; Laela, Sri; Putri, Nadia Oktiffany (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Background: overcrowded Emergency rooms have negative impacts on patients, staff, and the hospital system. These impacts on patients include delays in assessment and receiving necessary care, increased frequency of exposure to errors, and including error treatment, reduce satisfaction patient, improvement long care stay and results Which worsening, as well as increased inpatient mortality. Impacts on ER staff include increased work stress and fatigue, increased exposure to violence, and non-compliance with standard operating procedures during times of overcrowding.Objective: This study aims to determine the effect of overcrowding on nurses' work stress and patient satisfaction in the Emergency Room of Hermina Jatinegara Hospital.Method: This research uses quantitative research with a cross-sectional approach. sectional. The population of this study are all the nurses who work in the Emergency Room of Hermina Jatinegara Hospital, totaling 28 nurses, the nurse sampling method used a total sampling technique of 28 respondents, and the patient sampling method used a purposive sampling technique of 366 patients. The statistical test used chi-square test. square. Data analysis using SPSS software.Result: there is an overcrowded effect on work stress of nurses in the Emergency Room of Hermina Jatinegara Hospital (p value = 0.04), and there is an influence of overcrowding on patient satisfaction at the Emergency Room of Hermina Jatinegara Hospital (p value = 0.000).Conclusion: Overcrowded assessment Using the NEDOCS assessment, it was found that most of the categories were not busy, most of the nurses working in the ER experienced low category work stress , almost all patients who visited the ER were satisfied with the services in the ER, and the influence of overcrowding on nurses' work stress and patient satisfaction in the Emergency Room of Hermina Jatinegara Hospital.